Meningkatkan Kemampuan Operasi Hitung Perkalian pada Peserta Didik Disabilitas Intelektual Melalui Media Digital Kantong Perkalian - Trioktafia, Shintia; Efrina, Elsa; Iswari, Mega; Taufan, Johandri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to improve the multiplication skills of seventh-grade students with intellectual disabilities at SLB Negeri 1 Harau through the use of digital multiplication pocket media. The study used a quantitative approach with an experimental method in the form of Single Subject Research (SSR) with an A–B design. The research subject was one seventh-grade student with intellectual disabilities. Data collection was carried out through a multiplication ability test consisting of 34 questions given at each meeting. The data were analysed descriptively using visual analysis of graphs in the form of percentages. The research was conducted over 10 meetings consisting of two phases, namely the baseline phase (A) and the intervention phase (B). In the baseline phase, which lasted for four meetings, the percentage of multiplication skills ranged from 38% to 47%. After the intervention using digital multiplication bags for six meetings, the percentage of ability gradually increased to 100%. The results showed that the use of digital multiplication bags was effective in improving the multiplication skills of students with intellectual disabilities. These findings indicate that visual and interactive digital media can help students understand the concept of multiplication more concretely and meaningfully.